When is market the benchmark? Reinforcement evidence from repurchase decisions - Jiao, P; Nax, H (University of Oxford, 2016)
Reinforcement relative to an adaptive benchmark is a well-established model of behavior outside finance. Recently, reinforcement has been identified as an important driver of decisions to repurchase a stock. In this paper, we enrich the existing reinforcement model of repurchasing by an aspiration-based market benchmark. When choosing which stock to repurchase, investors' sources of reinforcement are weighted averages of absolute returns from previous sales and relative returns with respect to a market benchmark. The weights change according to market environments. We empirically identify the following crucial asymmetry that cannot be reconciled by simple reinforcement strategy, but is consistent with the model we propose: investors place more weight on relative returns when the market is performing well, and place more weight on absolute returns when the market is performing badly.